COMPARATIVE ANALYSIS OF COMPANY PERFORMANCE BEFORE AND AFTER MERGERS AND ACQUISITIONS IN COMPANY LISTED ON IDX 2018-2021 - Edrick, Jon; Wijaya, Andi (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study is to examine how companies trading on the Indonesia Stock Exchange fared before and after M&A deals were made in the years 2018 through 2021. In this Study, we employed a comparable quantitative approach called